VERTICAL ACTIVITY ESTIMATION USING 2D RADAR - Hakl, Henri; Le Roux, Willem (Scientia Militaria - South African Journal of Military Studies, 2011)
Understanding airspace activity is essential for airspace control. Being able to detect vertical activity in aircraft allows prediction of aircraft intent, thereby allowing more accurate situation awareness and correspondingly more appropriate airspace control response. The method for qualitative vertical activity estimation as presented is characterised by a very fast response time and requires minimal sensor input. The method relies on the interplay of two opposing motion prediction models. The efficacy of the method is demonstrated in both simulated and real-world data.